2021
DOI: 10.1002/elps.202100168
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing affinity‐based electroanalytical biosensors by integrated AC electrokinetic enrichment—A mini review

Abstract: Biosensors play a central role in moving diagnostics to being on‐site or decentralized. Affinity biosensor, an important category of biosensors, has important applications in clinical diagnosis, pharmaceuticals, immunology, and other fields. Affinity biosensors rely on specific binding between target analytes and biological ligands such as antibodies, nucleic acids, or other receptors to generate measurable signals. Oftentimes the target analytes in practical samples are of low abundance in a complex matrix. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Enrichment of samples was employed when the sensing platform was directly affected by the sample ingredients. 8,9 Magnetic enrichment can depend on specific or non-specific methods of target analysts. [10][11][12] Most of the biosensors were based on the immunoaffinitybased platforms, such as optical, electrochemical or ELISA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enrichment of samples was employed when the sensing platform was directly affected by the sample ingredients. 8,9 Magnetic enrichment can depend on specific or non-specific methods of target analysts. [10][11][12] Most of the biosensors were based on the immunoaffinitybased platforms, such as optical, electrochemical or ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of samples was employed when the sensing platform was directly affected by the sample ingredients. 8,9 Magnetic enrichment can depend on specific or non-specific methods of target analysts. 10–12…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of pumps and electric fields for reasons of mixing rather than simple locomotion would be classified as an active mixing system [ 25 ]. AC electrokinetic and its implications in biosensors is a growing field of research with proof of principle experiments that has shown a decrease of the limit of detection by several orders of magnitude and decreased the detection time from hours to minutes [ 26 , 27 ]. The most frequently applied methods to increase the mass transfer and achieve an enrichment of analytes on the sensor surface are AC electroosmosis, AC electrothermal effect [ 28 , 29 ] and dielectrophoresis (DEP).…”
Section: Introductionmentioning
confidence: 99%
“…While previous reviews have covered generally AC electrokinetic enhanced biosensors [ 26 , 27 ], DEP in microbial sensors [ 34 ] or the detection of biomarkers [ 35 ], we are here aiming to cover biosensors assisted with DEP in the light of new theoretical approaches, recent examples and critically discuss their potential to increase sensitivity and to decrease the assay time of biosensors. Key aspects in this endeavor are an improved mass transfer and the avoidance of nonspecific bindings.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are expensive and time‐consuming, which restricts their practical applications. A better understanding of BPA exposure levels requires field‐deployable instruments that can be used to monitor BPA levels on‐site in living environments [10] . A sensitive and simple method using easy‐to‐operate readout equipment is needed to detect BPA practically.…”
Section: Introductionmentioning
confidence: 99%